Earlier surgery improves long-term survival compared to class I surgical indications and infective endocarditis surgery for isolated severe tricuspid regurgitation. (25th November 2020) - Wang, T.K.M; Akyuz, K; Xu, B; Gillinov, M; Pettersson, G; Griffin, B.P; Desai, M.Y
Abstract: Background: Isolated tricuspid surgery has markedly higher mortality rates (9–10%) in contemporary national registries compared to other single-valve operations. The optimal timing and indications remain controversial, and earlier surgery before developing ESC guidelines class 1 indications may improve the survival for isolated severe tricuspid regurgitation. Purpose: We aimed to compare the characteristics and outcomes of isolated tricuspid regurgitation (TR) surgery by indication. Methods: Consecutive patients undergoing isolated tricuspid valve surgery for TR without other concomitant valve surgery at Cleveland Clinic from 2004 to 2019 were studied. Indications were divided into group 1: ESC guidelines class 1 (severe symptomatic TR), group 2: infective endocarditis, and group 3: non-class 1 (asymptomatic severe TR with or without right ventricular dilation and/or dysfunction) and no endocarditis, for comparative analyses of characteristics and outcomes. Results: The study included 207 patients (group 1: 115, group 2: 48 and group 3: 44) with mean age 54.1±17.8 years, 116 (56.0% females and 151. Tricuspid repair was performed in 72.9% (73.0%, 66.7% and 79.5% for Groups 1–3, P=0.381). Group 3 patients were younger, had higher prevalence of primary TR, lower prevalence of heart failure, atrial fibrillation, chronic lung disease, cirrhosis, renal impairment, right ventricular and left ventricular dysfunction than Group 1. Overall operative mortality rates were 4.9% ( group 1: 7.0%, group 2: 4.2% and group 3: 0.0%), while mortality during follow-up of 3.3±4.0 years was lower for group 3 than for groups 1 or 2 (Figure 1). Independent predictors of long-term mortality were Group 1 compared to Group 3 and reduced estimated glomerular filtration rate. Conclusion: Patients without class I or endocarditis indications had superior unadjusted and adjusted survival compared to those with these indications. The high mortality rate of isolated TR surgery may be reduced by both earlier surgery and being performed at an experienced cardiac surgery center. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): National Heart Foundation of New Zealand - Overseas Clinical and Research Fellowship